Linguistic and Extralinguistic Media of Social Representations in the Public Discourse - Zbróg, Zuzanna; Zbróg, Piotr (Respectus Philologicus, 2017)
The aim of the article is to present the utility of the social representation theory as a theoretical and methodological basis of the public discourse research. The theory, enunciated by the French psychologist Serge Moscovici, offers a new approach to the research of the way in which the media and communities / social groups construct the understanding of the issues which are important to them. The analysis of public discourse conducted within the framework of this theory is based on the observation of linguistic media with which the processes of anchoring (naming, emotional anchoring, thematic anchoring, anchoring by metaphors, anchoring in antinomies) and objectification (emotional objectification, personification) are conducted. They constitute the basic communicative mechanisms which produce social representations. The role of language as a medium of social representation will be emphasised. The article will also discuss the extralinguistic media of social representations which determine the overall image of discursive social reality. Social representations may be perceived as a tool for description and understanding of reality.